Cobalt-Copper Oxide Catalysts for VOC Abatement: Effect of Co:Cu Ratio on Performance in Ethanol Oxidation - Kupková, Květa; Topka, Pavel; Balabánová, Jana; Koštejn, Martin; Jirátová, Květuše; Giraudon, Jean-Marc; Lamonier, Jean-Francois; Maixner, Jaroslav; Kovanda, František (Catalysts, 2023)
The effect of the Co-Cu oxide catalysts composition on their physicochemical properties and performance in the deep oxidation of ethanol was studied. The catalysts with Co:Cu molar ratios of 4:1, 1:1, and 1:4 were obtained by calcination (4 h at 500 °C in air) of the coprecipitated precursors and characterized in detail using powder XRD, Raman spectroscopy, N2 physisorption, H2-TPR, and XPS. The powder XRD and Raman spectroscopy indicated the formation of Co3O4 and CuO mixtures rather than Co-Cu mixed oxides. The CuO promoted the Co3O4 reduction; the Co-Cu catalysts were reduced more easily than the single-component Co and Cu oxides and the main reduction maxima were shifted to lower temperatures with increasing cobalt content in the catalysts. The Co-Cu oxide catalyst with a Co:Cu molar ratio of 4:1 exhibited the best performance in ethanol gas-phase oxidation, showing the lowest T50 (91 °C) and T90(CO2) (159 °C) temperatures needed for 50% ethanol conversion and 90% conversion to CO2, respectively. The excellent catalytic properties of this Co-Cu oxide catalyst were ascribed to the synergistic effect of Co and Cu components. The high activity and selectivity of the Co-Cu catalyst was attributed to the presence of finely dispersed CuO particles on the surface of Co3O4.